Upaya Peningkatan Kesadaran Mahasiswa dalam Melestarikan Warisan Budaya Lokal melalui Pelatihan Canting Batik di Sanggar Batik Seni Pendopo - Apriansyah Sipayung; Amelya Putri Suwandana; M Haikal Aprilianto; Khafi Puddin; Aprinawati Aprinawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Batik is one of Indonesia's intangible cultural heritages recognized by UNESCO since 2009. However, along with the rapid pace of globalization, the interest of the younger generation in preserving local culture has declined. This study aims to analyze how canting batik training at Sanggar Batik Seni Pendopo can increase students' awareness of local cultural preservation. This research uses a descriptive qualitative approach focused on personal experience (personal experience method), where the author directly participates in the training activities as both a participant and an observer throughout the entire Canting Batik Training organized by Sanggar Batik Seni Pendopo. This research was conducted at Sanggar Batik Seni Pendopo in Perum Ray Pendopo 3, Jl. Siabu Dusun 2, Bandar Setia, Medan. The training was attended by 60 students from the Entrepreneurship Study Program at Universitas Negeri Medan. The research results indicate that the direct involvement of the authors provides a deeper empirical perspective on the process of enhancing participants' knowledge. Batik canting training not only improves technical skills but also fosters philosophical understanding, moral values, and awareness of the importance of preserving cultural heritage. Students become more proud of the works they create and develop a strong desire to preserve batik through modern batik innovations.